Meta-Analysis Study of Correlation Between Olfactory Dysfunction and Cognitive Impairment in Parkinson's Disease - Juliana Sie; Junita Maja Pertiwi; Rizal Tumewah; Ansye Momole; Seilly Jehosua; Windy Wariki (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
Disturbance in olfactory perception is commonly identified as a non motor manifestation in Parkinson’s disease and is often interpreted as an early biological signal reflecting ongoing degeneration of neural structures. This study was specifically formulated to conduct an in depth evaluation of the association between reduced smell performance and impaired cognitive functioning in Parkinson’s disease by applying systematic numerical aggregation techniques that adhere to internationally accepted research protocols. A broad and methodologically organized literature exploration was conducted using PubMed Wiley and ScienceDirect to identify empirical studies examining the association linking smell processing ability with mental functioning measures in individuals diagnosed with Parkinson’s disease. The screening process was carried out in accordance with clearly defined inclusion requirements. Assessment of smell function relied on the olfactory recognition assessment developed by the University of Pennsylvania Test UPSIT while evaluation of cognitive condition employed the MMSE alongside the MoCA cognitive screening tools. Pooled odds ratio values along with 95% confidence interval ranges were calculated using a random effects modeling framework. Overall 3 eligible studies comprising 773 individuals conducted in populations from America, Korea, and Britain met the established inclusion standards. Quantitative synthesis revealed a statistically meaningful relationship between impaired olfactory ability and reduced cognitive performance in Parkinson’s disease, with individuals experiencing hyposmia or anosmia showing a markedly increased probability of cognitive impairment compared with participants exhibiting intact smell perception OR 2.57 95% CI 1.15 to 5.74. The results of this analysis suggest a strong and statistically significant relationship between diminished olfactory capacity and cognitive impairment in Parkinson’s disease, highlighting its potential role as an early detectable clinical indicator of progressive cognitive deterioration. Despite the presence of variability among included studies and a relatively small pool of eligible research, the meta analytic evidence supports the usefulness of olfactory assessment as a non invasive and economically efficient approach for identifying cognitive risk in Parkinson’s disease. Additional large scale investigations employing uniform evaluation protocols are necessary to confirm these outcomes and enhance their relevance in clinical practice.